PUASA PADA KEBUNTINGAN TRIMESTER 1, 2 DAN 3 RELATIF AMAN DILIHAT PADA INDEKS APOPTOSIS SEL NEURON OTAK RATTUS NORVEGICUS BARU LAHIR - Wati, Yunita Kholilaili Saras; Joewono, Hermanto Tri; Miftahussurur, Muhammad (Care : Jurnal Ilmiah Ilmu Kesehatan, 2021)
Fasting in pregnancy that can increase neural network activity in the brain region and produce BDNF secretions that seek survival pathways will produce pro survival / anti apoptosis in cerebral neuron cells and the cerebellum. The aim of this study to analyze the effect of fasting during pregnancy on the index of apoptosis of cerebral neuron cells and the cerebellum of the newly born Rattus norvegicus. This research was using Experimental laboratory studies that were correct with the post test study design were only the control group design using experimental animals Rattus norvegicus at the Pathology Laboratory of the Faculty of Medicine, Airlangga University Surabaya which were collected into 3 research groups (1st, 2nd, and 3rd trimesters) and 1 control group . Each group consisted of 6 Rattus norvegicus mothers. The brain dissection of the newborn Rattus norvegicus child was taken and the apoptotic index was calculated using the Immunohistochemical Tunnel method. and discuss with the Immunoreactive Score (IRS). The results of the Kruskal wallis analysis were expressed as the Cerebrum apoptosis index in all four groups (p 0.05). Most apoptosis in the cerebrum was in the first trimester (3.9) and lowest in the second trimester (1.5). The results of the cerebellar apoptosis index analysis by the Kruskall wallis test proved that the most cerebellar apoptosis in the first trimester (4.87) and the lowest in the second trimester (1.33). Conclusion there is no difference between the 1,2 th trimester and 3 in the control of the cerebrum and cerebellum